Development of Problem-Based Learning E-Modules with a Stem Approach to Increase the Learning Motivation of Grade VI Elementary School Students in Piyungan District - Shafarina, Annisa Yola; Putra, Feragi Azizun; Setiyono, Setiyono; Putri, Reza Mareta (Gema Wiralodra, 2025)
This research aims to 1) produce PBL-Based E-Modules with a STEM approach that meets the eligibility criteria, and 2) determine the effectiveness of PBL-Based E-Modules with the resulting STEM approach to increase the learning motivation of grade VI students of SD Sekecamatan Piyungan. This research is Research and Development (R&D) using the ADDIE model which consists of analysis, design, development, implementation, and evaluation. Product feasibility tests are carried out by media expert validators and material expert validators. The subjects of the one-to-one trial were three students and 1 teacher at SD Muhammadiyah Karangploso. The subjects of the small group trial were 23 students of SD Negeri Piyungan Class A. The subjects of the field trial were 25 students of SD Negeri Piyungan class B as the control class and 27 students of SD Negeri Mandungan as the experimental class. Data collection using interview guidelines, observation guidelines, product assessment sheets, teacher response scales and student response scales, and learning motivation scales of grade VI elementary school students were analyzed using a t-test. The results of the study showed that: (1) The PBL-based e-module with the resulting STEM approach met the criteria of "Very Feasible" according to the assessment of media experts and subject matter experts, in the one to one trial obtained the category of "Very Feasible" from the responses given by the teacher and obtained the category of "Feasible" from the students' responses, while in the small group trial obtained the category of "Very Feasible" from the responses given by the teacher and obtained the category of "Feasible" from the responses of the students; (2) PBL-based E-Module with a STEM approach in significantly increasing the learning motivation of grade VI elementary school students with a significant score of 0.000 < 0.05